2021
DOI: 10.1186/s42836-021-00075-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of assembly forces during creation of head-neck taper junction considering soft tissue bearing: a biomechanical study

Abstract: Background All current total hip arthroplasty (THA) systems are modular in design. Only during the operation femoral head and stem get connected by a Morse taper junction. The junction is realized by hammer blows from the surgeon. Decisive for the junction strength is the maximum force acting once in the direction of the neck axis, which is mainly influenced by the applied impulse and surrounding soft tissues. This leads to large differences in assembly forces between the surgeries. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…This was an expected result, as the testing machine was regulated to a target force of 2 kN. In a study by Nassutt et al [14], the mean measured forces during joining by different test persons were 2927 ± 2059 N. Wendler et al [13] determined forces of 2037.2 N ± 724.9 N. These studies show that the standard deviation for the impaction forces on conventional joining methods is significantly higher than in our tests with the instrument and the previously joined head/adapter sleeve assembly. The surgeons in the study by Nassutt et al carried out 3-5 tests in their own test series and the standard deviation varied between 21 and 1414 N. This indicates that some surgeons generate repetitive reproducible joining forces while others have a more significant variation.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This was an expected result, as the testing machine was regulated to a target force of 2 kN. In a study by Nassutt et al [14], the mean measured forces during joining by different test persons were 2927 ± 2059 N. Wendler et al [13] determined forces of 2037.2 N ± 724.9 N. These studies show that the standard deviation for the impaction forces on conventional joining methods is significantly higher than in our tests with the instrument and the previously joined head/adapter sleeve assembly. The surgeons in the study by Nassutt et al carried out 3-5 tests in their own test series and the standard deviation varied between 21 and 1414 N. This indicates that some surgeons generate repetitive reproducible joining forces while others have a more significant variation.…”
Section: Discussionmentioning
confidence: 80%
“…The influence of the environment on the connection quality as an attenuating component was also not investigated in detail in this study. Some studies on this have come to different conclusions [13,31]. The number of test samples available for the experiments was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wendler et al reported a less severe attenuation at the implant neck that was 84.4% ± 13.5% of the introduced mallet force during head taper assembly on human cadavers [12]. They attributed the attenuation to their bearing of the handheld impactor or a misalignment between the impact direction and the neck axis [12].…”
Section: Plos Onementioning
confidence: 99%
“…To improve the force at the Points of Interest (PoI) like the implant-bone interface or the taper junction between head and stem, the force transmission from the mallet or the automated tool to the PoI must be understood. Common methods to measure the impaction force along the transmission path are instrumented mallets [4,6], instrumented broach handles [7], instrumented impactors [8], instrumented head impactors [9][10][11], load cells in the stem [5,12] or beneath the experimental setup. All of the above have in common, that the Position of Measurement (PoM) cannot be the same as the PoI.…”
Section: Introductionmentioning
confidence: 99%